Clarivate Research Fronts in the Digital Education: Perspectives from Asean Higher Education System - Chung, Nguyen Huu Thanh; Cam, Tran Ai (Journal of Ecohumanism, 2024)
This study examines impacful research fronts within the digital educational ecosystem, focusing on contributions from ASEAN higher education institutions. Using Clarivate Analytics' bibliometric methodologies, the five hot research research fronts —including Online Learning, Artificial Intelligence, Collaborative Learning, Virtual Reality, and Educational Technology—are explored and analyzed through core indicators such as Citation (Pciting), Productivity (Pcore), and Trajectory (Tciting), alongside the CPT index to measure impact. ASEAN universities, particularly in Malaysia and Indonesia, demonstrate notable productivity in Online Learning and Collaborative Learning. Malaysia ranks 4th globally in Online Learning, while Indonesia follows in 5th place. However, ASEAN contributions in Virtual Reality, Educational Technology, and Artificial Intelligence remain limited, highlighting opportunities for growth. The study underscores the need for ASEAN universities to enhance research capacity, foster regional collaboration, and focus on emerging fields like Virtual Reality and Artificial Intelligence. Targeted efforts will enable ASEAN institutions to strengthen their global impact and address regional educational challenges effectively.